Systemic Lupus Erythematosus (SLE) dengan Dugaan Anemia Hemolitik Autoimun (AIHA): Sebuah Laporan Kasus - Nely Masruroh Rosyidi; Irawan Fajar Kusuma (Jurnal Klinik dan Riset Kesehatan, 2026)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease widely prevalent worldwide. Hematological abnormalities, one of them being AIHA, are commonly observed among SLE patients and brings about high morbidity rates. We present a 27-year-old woman with complaints of fatigue, dizziness, nausea, vomiting, body pain, and shortness of breath who came to the emergency department with 13 prior hospitalizations. She was present with SLE-related symptoms such as facial rash upon sun exposure, diffuse body pain mainly pronounced in her fingers, reddish-brown urine, hair loss, and fatigue. Physical examination observed stable vital signs yet copious purpura on her extremities. Facial examination revealed mild edema with rashes. Lab results show severe anemia with hemoglobin level of 5.2g/dL, hematocrit of 14.5%, a markedly reduced erythrocyte count of 1.24 x 10⁶/µL, and an elevated bilirubin level. She has been diagnosed with SLE with a positive ANA test and a homogenous speckled pattern consistent with SLE. The patient received intravenous methylprednisolone as first-line treatment as well as leukodepleted packed red blood cells, which she responded positively. The absence of key diagnostic tools in Indonesian hospitals remain as a challenge, particularly in cases where early recognition and timely treatment initiation is crucial. Keywords: Systemic Lupus Erythematosus; Autoimmune Hemolytic Anemia